Machines of war the definitive visual history of military hardware (Dorling Kindersley Limited, 2017)
Explore the military vehicles, artillery, and industrial weaponry that changed the course of history. Discover vehicles from the Industrial era, World War I, World War II, the Cold War, and the modern world. Look up-close at the Gatling gun, the Spitfire fighter plane, the T-72 Tank and many more with virtual tours putting you at the helm of war's most formidable weapons.